GENETIC PARAMETERS OF FIELD SURVIVAL IN STRIPED CATFISH (Pangasianodon hypophthalmus) - Nguyen Van Sang; Phuc Huu Tran; Vu Thanh Nguyen; Nelson Howard Kasigwa; Tham Thi Hong Vo; Khoa Dang Phạm; Hung Dinh Nguyen (Indonesian Aquaculture Journal, 2022)
Grow-out or field survival (GS) is one of the most important traits of striped catfish. Genetic parameters of GS in generation 4 of the growth selected population of this species were estimated based on the data of 8,004 tagged and stocked and 6,410 harvested fish representing 152 full-sib and half-sib families. The heritability and estimated and realized correlated responses for GS, its phenotypic or genetic correlations with harvest weight (HW) and other growth traits, and direct realized response for HW were calculated. The low and significantly different from zero heritability for GS (0.12±0.05) was estimated. The medium positive and no significant difference from zero genetic correlation between GS and HW was found, 0.41±0.24. The estimated selection responses with the proposed selection proportion of 13.0% for GS was 8.5% in trait unit. Current and accumulated correlated selection responses for GS were -7.8% and -1.6%, and 25.5% and 47.6%, respectively, by Estimated Breeding Value and Least Square Means estimation methods. In addition to these results, the high heritability and direct estimated and realized responses for HW pose a great potential for applying multi-trait selection, including both GS and HW in G4 and in the long run.